The Evolution and Geographic Distribution of Headache Medicine Fellowship Programs and Graduates: An Observational Study. Issue 10 (November 2014) - Rizzoli, Paul; Weizenbaum, Emma; Loder, Thomas; Friedman, Deborah; Loder, Elizabeth
Abstract : Objectives: We sought to assess the experiences, growth, and distribution of accredited headache medicine fellowships since accreditation began in 2007, and to examine the number and current practice locations of fellows graduated from those programs. Background: There are no data on the distribution of headache fellowship programs and their graduates throughout the United States. Methods: We surveyed directors of Headache Medicine fellowship programs accredited by the United Council of Neurologic Subspecialties as of April 1, 2014. We recorded the geographic locations of accredited programs and fellowship graduates and determined their distribution in relation to the overall and selected minority populations of US census divisions, regions, and states. Results: In early 2014, there were 25 accredited Headache Medicine fellowship programs in the United States. Thirty‐two (63%) US states lack a headache fellowship program and 24 (47%) do not have a practicing United Council for Neurologic Subspecialties fellowship graduate. Fifty‐two of 96 fellows (54%) entered practice in the same state where they did their training. The northeastern United States has the best ratio of fellowship programs and graduates to population (0.28 and 0.35 per million inhabitants) and land area (6.38 and 8 per 100, 000 square miles). The Pacific Northwest has the worst (0.05 and 0.02 fellowship programs and graduates per million inhabitants and 2.3 and 1.1 per 100, 000 square miles). Fifty‐five percent of the US Hispanic population lives in areas of the country with only 32% of practicing certified headache specialists, 28% of accredited fellowship programs, and which have attracted only 27% of fellowship graduates. Thirty‐three percent of the US black population lives in areas with just 8% of fellowship programs and 27% of fellowship graduates. Fellowship directors report that funding for fellowship positions is an important challenge. Conclusions: The number of fellowship programs has increased dramatically since 2007, but their geographic distribution is uneven and so are the subsequent practice locations of fellow graduates. At present, the distribution of training programs and headache specialists is not well matched to the US population as a whole or to the location of important racial and ethnic minorities. Increasing the overall supply of headache specialists is important, but geographic inequalities in specialist distribution must also be addressed or disparities will increase.